CARRY-OVER OF AFLATOXIN B1-FEED INTO AFLATOXIN M1-MILK IN DAIRY COWS TREATED WITH NATURAL SOURCES OF AFLATOXIN AND BENTONITE - Sumantri, I.; Murti, T.W.; van der Poel, A.F.B.; Boehm, J.; Agus, A. (Diponegoro University, 2012)
High occurrence of aflatoxin contamination in feed stuffs implicates for a long time experience ofaflatoxin B1 (AFB1) exposure to dairy cattle in Indonesia. A latin square 4X4 research design wasadopted to study the characteristic of AFB1 carry-over rate (COR) of Indonesian crossbred FriesianHolstein (PFH) as effects of inclusions of AFB1-naturally contaminated feed and bentonite in the diet.Results showed a rapid aflatoxin M1 (AFM1) excretion in the milk, detected in the first milking sampleor 10 hours after AFB1 ingestion. The steady state of AFM1 concentration observed since the first dayof treatment period and AFM1 contamination was still detected until 5 days after AFB1 removed fromthe diet. The COR in this study was observed 0.1%. AFM1 concentration was highly significantly(P<0.01) affected by treatments. However, there were no significant effects (P>0.05) of levels of AFB1and bentonite inclusions on the COR, nutrients intake, milk production, and milk composition. IIt isconcluded that AFM1 concentration was influenced by AFB1 intake and that transfer of AFB1-feed intoAFM1-milk (COR) in PFH cow was lower compare to reported COR value for dairy cow in sub tropicalregion.